Authority, trust and accountability : regulation of pharmaceutical drug trade practices in Yeoville. - Cossa, Ema Euclesia (My University, 2013)
The increase in use and distribution of pharmaceuticals on a global scale has caused pharmaceuticals to play an integral role in the notions of quality of health. This study is concerned with how Western medication is transacted and interpreted in explicit and implicit contrast to the other context. I observe the commercial trade of medicines, specifically the effects of regulation of pharmaceutical drug trade in a suburb of Johannesburg (Yeoville) a low income area where many migrant groups have found long and short term refuge. A Policing and Mobility Project (Hornberger & Cossa 2010) centred on tracing paths of medication and the level of policing thereof in Johannesburg revealed that clandestine sale of medication occurs in the suburb’s local market. This prompted a comparison between the formal and informal pharmaceutical trade spaces. Simon (a pharmacist) and Teresa (a former nurse turned market trader) sell pharmaceutical drugs in seemingly contrasting contexts. Despite their expertise in health care, Simon and Teresa were flung to opposite ends of the trade spectrum by regulation. In the weeks I spent with Teresa and Simon it became abundantly clear that the spaces which had been initially presented as the opposite of one another may have had a few layers of common ground. At first it seems as though only regulation has the ability to produce authority, trust and accountability. But later it becomes evident that such aspects can be reproduced through manipulation of everyday practices. Roger Cotterrell’s (1999) interpretation of Emile Durkheim’s view of the law as a ‘Social Fact’ (1999:9), demonstrates how the collective experience of regulation (an aspect of the law) affects the individual. But De Certeau (1984) claims that the same individual can tacitly undermine this collective experience (the dominant form) through everyday practices. The findings suggest that the assumed roles of regulated and unregulated pharmaceutical trading spaces are not as static as they appear. The study concluded that authority, trust and accountability can be reproduced outside of regulation. And secondly thus the formal and informal trade of pharmaceuticals in Yeoville have more in common than perceived since both Simon and Teresa, had authority in health, their customer’s trust and loyalty and were accountable within the trade.
Keywords: Pharmaceutical industry--South Africa.; Pharmaceutical industry--Government policy--South Africa.